Rola informacji w funkcjonowaniu przyrody w kontekście sporu o ewolucję - Giertych, Maciej (Filozofia Nauki, 2001)
Biological reality does not consist of chemistry and physics of organism alone. It also includes their information content. This information regulates developmental and reproductive processes. Its quantity is finite. We observe mixing of information (mating patterns, reduction division, hybridisation, genetic engineering), its loss (species extinction, reduction of genetic diversity in domestication, isolation, inbreeding) and increase of useless or injurious information (duplications, neutral and harmful mutations, genetic load). On the other hand we do not observe new useful biological information arising (positive mutations). New useful information does not appear by accident. Nature and man made selections reduce the information resources, mutations debilitate them, population reduction and its isolation cause accidental losses of information. Acquired resistance to antibiotics or herbicides, which is often presented as an example of increase of information, is only a defence mechanism against loss of functionality of an organism or population (e.g. by immunological adaptation). Such mechanisms belong to the already existing information content. No new organs or functions are produced. Until natural sciences come up with an indication of the mode by which useful information resources can be increased in nature, by which new functions or organs are produced, the theory of evolution will remain a hypothesis without substantiation in facts.